APLIKASI PANDUAN KODE ERROR PADA MESIN ATM WINCOR NIXDORF PROCASH 280 PART CONTROLLER CMD BERBASIS MOBILE - Hari Suryantoro; Dartono Dartono; Dwi Saputra (Institut Teknologi dan Bisnis Swadharma, 2022)
With the many types of machines on the Procash 280 issued by PT. Wincor Nixdorf sometimes engineers cannot understand each type of ATM and memorize the codes on the Wincor Nixdorf brand ATMs and also the error codes in these different ATMs as a guide for engineers in the field in today’s digital era, there needs to be a mobile-based application that can be installed and used through a smartphone-based on a user interface and GUI, a mobile application itself is an application made for mobile devices such as smartphones, tablets, and others by using certain programming languages so that can be used and taken anywhere that helps as a manual or handle to make it easier for engineers to find out the error code on the Wincor Nixdorf Procash 280 ATM on the part controller in general and specifically for new engineers so that there is standardization in handling error codes that make it easier and shorten the working time in knowing existing error code